THE USE OF TURN-TAKING STRATEGY BETWEEN INTROVERTED AND EXTROVERTED STUDENTS IN ENGLISH AS FOREIGN LANGUAGE (EFL) - Soedarsono, Eva Nur (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
Language is the main aspect of education. Improving English as a foreign language (EFL) learners’ speaking skills is a crucial communication requirement. In speaking skills, aspects of speech such as pronunciation, intonation, tone, stress, and fluency are highly emphasized. Furthermore, mental processes such as understanding, reasoning, adapting, turn-taking, and responding also play an essential role in speech. Turn-taking is a hugely important thing in conversation, especially in discussion. To take a turn in conversation is a big deal. Personality should consider factors in learning a second language. Extroverts and introverts have different learning styles, which will affect their speaking English learning. This research aimed to seek the used turn-taking pattern and strategies between student extroverts and introverts. This research was conducted using a qualitative-descriptive approach design to the comprehensive summarization of specific events experienced by individuals or small peer groups. The subjects of this research were students in the English Education Department of Universitas Muhammadiyah Surabaya for the 2021 final examination. As a result, Extroverted students are more comfortable and eager to take the lead in initiating conversations and introverts are more comfortable in the role of responders. While introverts and extroverts utilize similar strategies for turn-taking, their implementation differs; introverts may employ structured pauses and thoughtful contributions, whereas extroverts often engage in dynamic and spontaneous exchanges to ensure active conversation participation.